Motivasi Kebangkitan Dunia Islam pada Aabd XIX-XX - Dahlan M, Muh. (Rihlah: Jurnal Sejarah dan Kebudayaan, 2015)
The purpose of this essay is to describe the motivation of the resurrection in Islamic World in the XIX – XX century. As well as we know, after three great kingdoms in the Islamic world (Ottoman, Safavid and Mughal) suffered a setback, Countries in Europe appeared to be a new power in the world in the XIX century. This situation caused Muslims become a minority and marginalized people in the world. However, the motivation to restore the glory of Islam still exists because of the strong impulsed of the Islamic doctrine. So gradually, the Muslims were able to rise again, either by way of modernization or purification of Islam. In fact, there are a lot Islamic countries with Muslims as a majority people in it, such as Saudi Arabia, Turkey, India (before India splited into Pakistan) and Indonesia.